Punching shear in reinforced concrete flat slabs with hole adjacent to the column and moment transfer - Oliveira,D. C. (2014)
The structural behavior and the ultimate punching shear resistance of internal reinforced concrete flat slab-column connections, with one hole adjacent to the column, with or without flexural moment transfer of the slab to the column was investigated. Main variables were: the existence whether or not hole, flexural reinforcement layout and ratio, the direction and sense of the moment transferred and the eccentricity of the load (M (moment transferred to column) / V (shear)) ratio at the connection - 0,50 m or 0,25 m. Seven internal slab-column joining were tested and ultimate loads, cracking, deflections, concrete and reinforcement strains were analyzed. The existence of hole adjacent to the smaller column dimension, the hole dimension, flexural reinforcement rate and placing, the variation of relation Mu/Vu in function of the load, and, than, of eccentricity of the load, influenced the slabs behavior and rupture load. Test results were compared with the estimations from CEB-FIP/MC1990 [7], EC2/2004 [12], ACI-318:2011 [1] and NBR 6118:2007 [5]. ACI [1] and EC2 [12] presented most conservative estimates, although have presented some non conservative estimates. Brazilian NBR [5], even though being partly based in EC2 [12], presented smaller conservative estimates and more non conservative estimates. A modification on all codes is proposed for taking in account the moment caused by the eccentricity at the critical perimeter for slabs with holes.